Implementation of Grapyak Semanak Culture-Based Character Strengthening in the Prevention of Psychic Violence among Blind Students (Thomas Lickona's Character Education Perspective) - Indonesia, Alvin Rajaswara; Septina Galih Pudyastuti; Yosafat Hermawan Trinugraha (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Psychological violence between students is a problem in the world of education and can occur between blind students in special schools. This study aims to explore the strategies, inhibiting factors, and implications of character strengthening based on grapyak semanak culture in preventing psychological violence between blind students at SLB A YKAB Surakarta. The informants involved in this study include three teachers of blind students and seven blind students of grade VI SDLB. Data collection was conducted through participant observation, semi-structured interviews, and documentation. The collected data were analyzed using an interactive model with the stages of data reduction, data presentation, and conclusion drawing. The results showed: 1) character strengthening based on grapyak semanak culture in the prevention of psychological violence among blind students at SLB A YKAB Surakarta is implemented by teachers through storytelling strategies and guidance and counseling; 2) inhibiting factors for strengthening grapyak semanak culture-based character in the prevention of psychological violence among blind students at SLB A YKAB Surakarta include the difficulty of blind students in regulating negative emotions and less than optimal synergy between parents and teachers of blind students; 3) Teachers' strategies in strengthening character based on grapyak semanak culture can have constructive-progressive implications for the majority of aspects in the grapyak semanak character component of visually impaired students, but not for aspects of moral awareness, self-control, and habits.